Project Rénard - Rodrigues, Pedro Inock Baptista, 1984- (2015)
During the 20th century some avant-garde movements had their expression in architecture. In general, these styles are influenced by the Bauhaus, and they are contemporary of it. The modern movement stood ground and is seen as a major influence throughout architectural history and contemporary tradition. The most controversial aspect of the modern movement was, and remains, its rejection of tradition. Some historians see the evolution of Modern architecture as a social matter, closely tied to the project of Modernity and thus the Enlightenment. The modernism as a movement then was afresh and new, undisturbed by present biasconfirming the reliability of the source. Understanding the concept of modernism in architecture, the opposing of traditional styles would be greatly enforced through Waiter Gropius and his Bauhaus perception. However, in contemporary society, there is ample evidence that function follows form, for without an understanding of form, we cannot derive function. Even so, there are some cases when form and function are one. So it can be argued that such criticisms don't hold much water in a genre that has always reinvented itself, borrowing and remixing until the question of authenticity is at best a slippery one. Why are we then, stuck with terms like "experimental" or "innovative" or maybe "post-Language"1? Do we see what we expect to see?